Biphasic Effect of Buspirone on the H-Reflex in Acute Spinal Decerebrated Mice - Develle, Yann; Leblond, Hugues (Frontiers in Cellular Neuroscience, 2020)
Pharmacological treatment facilitating locomotor expression also modulates reflex expression through the re-arrangement of spinal networks. Buspirone, a partial serotonin receptor agonist (5-HT1A), was recently shown to facilitate and even trigger locomotor movements in mice after complete spinal lesion (Tx). Here, we studied its effect on the H-reflex after acute Tx in adult mice. To avoid possible impacts of anesthetics on H-reflex depression, experiments were performed after decerebration in un-anesthetized mice (N=13). The H-reflex in plantar muscles of the hind-paw was recorded after tibial nerve stimulation 2 h after Tx at the 8th thoracic vertebrae. Average H/M ratio was compared before and every 10 min after buspirone (8 mg/kg, i.p.) for 60 min. Frequency-dependent depression (FDD) of the H-reflex was assessed before and 60 min after buspirone. Before buspirone, a stable H-reflex could be elicited in acute spinal mice and FDD of the H-reflex was observed at 5Hz (68%) and 10Hz (70%) relative to 0.2Hz. After buspirone, the H/M ratio was initially significantly decreased to 69% of pre-treatment. It then increased significantly 30 to 60 min after exposure to buspirone, reaching 170% 60 min after injection. This effect was not observed in a control group (saline) and was blocked when a 5-HT1A antagonist (NAD-299) was administered with buspirone. FDD 60 min after buspirone was not significantly different that FDD without treatment. Altogether results suggest that the reported pro-locomotor effect of buspirone occurs at a time where there is a 5-HT1A receptors mediated reflex depression followed by a second phase marked by enhancement of reflex excitability.